Estudio del conector - Mª Jesús Saló Galán (Çédille: Revista de Estudios Franceses, 2007)
We would like to present in this essay a description of the semantic and pragmatic function of the connector au fort in preclassic and classic French.Once the starting hypothesis is formulated, this connector is mainly registered within the category of reformulative connectors, we asked ourselves what kind of reformulation operations it introduced, and we studied them through the signs the different operations of this multipurpose connector leaves in speech.